Comparative Genome-Wide Alternative Splicing Analysis of Longissimus Dorsi Muscles Between Japanese Black (Wagyu) and Chinese Red Steppes Cattle - Fang, Xibi; Xia, Lixin; Yu, Haibin; He, Wei; Bai, Zitong; Qin, Lihong; Jiang, Ping; Zhao, Yumin; Zhao, Zhihui; Yang, Runjun (Frontiers in Veterinary Science, 2021)
Alternative splicing is a ubiquitous regulatory mechanism in gene expression that allows a single gene generating multiple mRNAs. Significant differences in fat deposition ability and meat quality traits have been reported between Japanese black cattle (Wagyu) and Chinese Red Steppes, which presented a unique model for analyzing the effects of transcriptional level on marbling fat in livestock. In previous studies, the differentially expressed genes (DGEs) in longissimus dorsi muscle (LDM) samples between Wagyu and other breeds of beef cattle have been reported. In this study, we further investigated the differences of alternative splicing in LDM between Wagyu and Chinese Red Steppes cattle. We identified several alternative splicing types including cassette exon, mutually exclusive exons, alternative 5' splice site, alternative 3' splice site, alternative start exon, and intron retention. In total, 115 differentially expressed alternatively spliced genes were obtained, of which 17 genes were enriched in the metabolic pathway. Among the 17 genes, 5 genes – malonyl-CoA-acyl carrier protein transacylase (MCAT), carnitine palmitoyltransferase 1B (CPT1B), hydroxyacyl-CoA dehydrogenase trifunctional multi enzyme complex subunit beta (HADHB), sirtuin 2 (SIRT2) and diacylglycerol O-acyltransferase 1 (DGAT1) – appeared to be the novel spliced candidates which affect the lipid metabolism in cattle. Additionally, another 17 genes were enriched in the GO terms related to muscle development, such as nuclear receptor subfamily 4 group A member 1 (NR4A1), ubiquinol-cytochrome c reductase complex assembly factor 2 (UQCC2), Y-box binding protein 3 (YBX3/ CSDA) and integrin subunit alpha 7 (ITGA7). Overall, altered splicing and expression levels of these novel candidates between Japanese black cattle and Chinese Red Steppes revealed by RNA-seq suggests their potential involvement in the muscle development and fat deposition of beef cattle.